2015
DOI: 10.1681/asn.2013091017
|View full text |Cite
|
Sign up to set email alerts
|

Localization of APOL1 Protein and mRNA in the Human Kidney

Abstract: Although APOL1 gene variants are associated with nephropathy in African Americans, little is known about APOL1 protein synthesis, uptake, and localization in kidney cells. To address these questions, we examined APOL1 protein and mRNA localization in human kidney and human kidney-derived cell lines. Indirect immunofluorescence microscopy performed on nondiseased nephrectomy cryosections from persons with normal kidney function revealed that APOL1 protein was markedly enriched in podocytes (colocalized with syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 33 publications
8
117
1
Order By: Relevance
“…APOL1 is predominantly present in the circulation and to a lesser extent in the liver and other solid organs, including the kidneys. Kidney APOL1 protein is enriched in glomerular podocytes, relative to proximal tubule and endothelial cells ( 5 ). Due to the abundance of APOL1 in human serum and uptake of free APOL1 into podocytes in vitro ( 5 ), it was initially hypothesized that circulating APOL1 protein might contribute to APOL1 -associated nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APOL1 is predominantly present in the circulation and to a lesser extent in the liver and other solid organs, including the kidneys. Kidney APOL1 protein is enriched in glomerular podocytes, relative to proximal tubule and endothelial cells ( 5 ). Due to the abundance of APOL1 in human serum and uptake of free APOL1 into podocytes in vitro ( 5 ), it was initially hypothesized that circulating APOL1 protein might contribute to APOL1 -associated nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…An N-terminal APOL1 (1-199 amino acids)-MBP fusion protein was obtained, as previously reported ( 5,15 ). cDNA corresponding to APOL1 (amino acid residues 13-130 of the APOL1 reference sequence) was generated by PCR and cloned into the 3 ) were pooled and separated by nondenaturing gradient gel electrophoresis to determine the elution position of APOL1.…”
Section: Co-immunoprecipitationmentioning
confidence: 99%
“…Because of the elevated risks for cardiovascular disease (CVD) and heart failure (HF) among people with chronic kidney disease compared with the general population,15 investigation of the cardiovascular risk of individuals who carry the APOL1 high‐risk variants is an issue of active study. Apolipoprotein L1 (Apol1) has been localized to endothelial and vascular smooth muscle cells within the kidney16, 17 and is also known to circulate in plasma with high‐density lipoprotein particles,18, 19 suggesting a potential role of the APOL1 risk variants in CVD. Studies to date on this topic, however, have been conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…APOL1 is expressed in medium-sized arterial and arteriolar endothelial cells in normal and diseased kidney sections (8). Ma et al identified APOL1 mRNA and protein expression in glomerular and interstitial endothelial cells (24). Consistent with these in vitro findings, a recent publication demonstrated that individuals with two APOL1 risk alleles exhibit a 2-fold increased risk of cardiovascular disease events compared with individuals with no risk alleles, irrespective of the presence of clinical kidney disease (25).…”
mentioning
confidence: 76%